Documentation Management Of Teacher Professional Education Program (PPG) For Pre-Service Teacher - Dwiyanti, Ulfa; Gabriel, Thomas (UHAMKA Press, 2023)
This study aims to determine the effect of online learning on the creativity of class XI students in the Accounting Skills Program at SMK PGRI 3 Jakarta in the 2020/2021 academic year. The population in this study were 300 people and 35 were taken as samples. The research method used is associative quantitative research method. The sampling technique used is purposive sampling. Data collected using a questionnaire/questionnaire. The results of this study indicate that there is an influence between online learning variables on students' creativity variables of 51.4%. Thus it can be stated that online learning has a strong enough effect on the creativity of students. Therefore, the results of this study concluded that there was an effect of online learning on the creativity of class XI students of the accounting expertise program at SMK PGRI 3 Jakarta. This is also evidenced by (Siregar dan Manurung, 2020) in their research detailing